Processing technology suitable for heat-conducting potting resin of new energy automobile driving motor stator
In the application of new energy vehicle drive motor stator, the thermal potting resin is prepared by using new processing technology to proportion raw materials, which solves the problem of difficult to take into account both the thermal conductivity coefficient and crack resistance, and achieves efficient potting and good motor performance.
Patent Information
- Application Number
- CN202411959176.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
In the application of new energy vehicle drive motor stator, the crack resistance and thermal conductivity are difficult to take into account, resulting in insufficient potting quality and reliability.
A new processing technology is adopted to prepare a thermally conductive potting resin with high thermal conductivity and good crack resistance by reasonably combining bisphenol A solid epoxy resin, toughening agent, modified filler and silane coupling agent.
The thermally conductive potting resin maintains good fluidity before curing, ensures potting quality and reliability, and reduces the vibration of the motor when the speed changes and the resistance of the cooling medium to the rotating part.
Smart Images

Figure BDA0005216664480000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal conductive potting resin materials, and in particular relates to a processing technology suitable for a thermal conductive potting resin for a stator of a drive motor of a new energy vehicle. Background Art
[0002] There are many studies on thermal conductive potting resins in China, but they mainly focus on the potting protection of electronic components. When these potting resins are used for smaller electronic components, as long as the toughening measures are appropriate, the cracking problem is generally not prominent. However, when used for large-sized motor windings, the potting glue shrinks during curing; the size change of the potting glue when the temperature changes is different from the motor core and winding. The larger the size of the workpiece, the greater the value of this difference, so the cracking phenomenon is more serious. After many trials of potting glue produced in China, including some products produced with imported technology, none of them did not crack, and some potting glue even cracked before it was completely cured.
[0003] Although the high thermal conductivity epoxy potting glue produced by a foreign company has good anti-cracking performance, the material viscosity is high, the resin fluidity is very poor, and the usable period is less than half an hour. For larger motors, there is no time to complete vacuum degassing and vacuum potting operations, resulting in a large number of bubbles and air gaps remaining inside the workpiece, and the potting quality and reliability cannot be guaranteed. In response to the above problems and the needs of new energy vehicle drive motor stator manufacturing, research on thermal conductive epoxy potting glue was carried out, focusing on ways to improve the potting glue's anti-cracking ability and thermal conductivity. Summary of the invention
[0004] In view of the fact that the thermal conductive potting resin currently suitable for the stator of the new energy vehicle drive motor has the problem of not being able to strike a good balance between anti-cracking performance and thermal conductivity, the present invention aims to provide a processing technology for the thermal conductive potting resin suitable for the stator of the new energy vehicle drive motor.
[0005] A processing technology for a thermally conductive potting resin for a stator of a drive motor for a new energy vehicle, wherein the thermally conductive potting resin comprises the following raw materials in parts by weight:
[0006] Component A: 60-100 parts of bisphenol A solid epoxy resin, 5-10 parts of toughening agent, 300-500 parts of modified filler, 1-3 parts of white carbon black, 7-12 parts of silane coupling agent KH550, 1-2 parts of defoaming agent;
[0007] Component B: 35-60 parts of curing agent, 0.3-0.8 parts of accelerator, 200-400 parts of modified filler, 1-4 parts of white carbon black, 6-10 parts of silane coupling agent KH550, and 1-4 parts of defoaming agent.
[0008] Furthermore, the toughening agent is ethylene-vinyl acetate copolymer, wherein the content of vinyl acetate is 18-25wt.%.
[0009] Furthermore, the preparation of the modified filler is as follows: the filler and the modifier are added to an isopropanol solution at a mass ratio of 100 to 120:1, ultrasonically dispersed at 40 to 55° C., the material is allowed to stand, filtered, the filter residue is dried, and after drying, ball milled to obtain the modified filler.
[0010] Furthermore, the modifier is a combination of hydrazine hydrate and trisodium citrate in a mass ratio of 5 to 8:1; and the filler is a combination of silicon carbide and hexagonal boron nitride in a mass ratio of 1:6 to 10.
[0011] Furthermore, the defoaming agent is a combination of polyether-modified heptamethyl trisiloxane and ethoxy-modified trisiloxane in a mass ratio of 12 to 20:1.
[0012] Furthermore, the curing agent is any one of dimethylaminopropylamine, dipropylenetriamine, and tetraethylenepentamine.
[0013] Furthermore, the accelerator is a combination of dibutyltin dilaurate and stannous octoate in a mass ratio of 3 to 5:1.
[0014] Furthermore, the processing technology of the heat-conducting potting resin suitable for the stator of the drive motor of the new energy vehicle comprises the following steps:
[0015] The preparation method of component A is as follows: add the above-mentioned proportion of bisphenol A type solid epoxy resin, toughening agent, modified filler, white carbon black, coupling agent, and defoaming agent into a stirring kettle, stir until completely dispersed and uniformly defoamed, and after defoaming is completed, component A is obtained.
[0016] The preparation method of component B is as follows: adding the curing agent, accelerator, modified filler, white carbon black, coupling agent and defoaming agent in the above proportion into a stirring kettle and stirring evenly; degassing the stirred glue solution uniformly, and after degassing, component B is obtained.
[0017] The thermal conductive potting resin is prepared by mixing the prepared component A and component B evenly, performing vacuum degassing, drying the stainless steel mold at 50-70° C., spraying a mold release agent on the stainless steel mold, pouring a thermal conductive potting glue solution, evacuating the mold, and curing in an oven, first curing at 70-80° C. for 1-2 hours, and then curing at 120-150° C. for 6-8 hours, to obtain the thermal conductive potting resin.
[0018] Compared with the prior art, the advantages of the present invention are:
[0019] (1) The heat-conductive potting resin provided by the present invention can maintain good fluidity before curing and penetrate into the uneven gaps on the winding surface. After potting, the outer surface of the workpiece should be smooth and flat, so that the rotating part of the motor has basically the same moment of inertia when rotating. It reduces the vibration caused by mechanical stress and thermal changes when the motor speed and direction suddenly change, and reduces the resistance of the cooling medium to the rotating part of the motor. In addition, it can be seen from the test that the heat-conductive potting resin provided by the present invention has a lower viscosity and a higher thermal conductivity for the motor winding. It can withstand cold and heat shocks and has both toughness and sufficiently high mechanical strength;
[0020] (2) The present invention uses isopropanol as an organic polar solvent, supplemented by the intercalation effect of hydrazine hydrate and trisodium citrate, and obtains BNNS with a well-preserved crystal structure after a long period of ultrasonic treatment and hydrothermal reaction. The two-dimensional BN is combined with the zero-dimensional filler silicon carbide SiC to improve the overall filling rate of the filler, which is conducive to the formation of a thermal conductive network, improve the thermal conductivity, and reduce the temperature difference between the inner and outer surfaces of the potting resin. On the one hand, the heat generated by the motor winding during operation can be quickly transferred to the outer surface of the workpiece. On the other hand, the internal stress caused by the temperature difference can be reduced;
[0021] (3) The present invention can directly affect the molecular weight and its distribution by controlling the vinyl acetate content in the ethylene-vinyl acetate copolymer. The larger the molecular weight, the longer the molecular chain, and the greater the intermolecular force that needs to be overcome during melting. Therefore, the higher the melting temperature, the wider the molecular weight distribution. The presence of low molecular weight components will reduce the overall melting temperature and improve the impact strength as a whole. DETAILED DESCRIPTION
[0022] The following is a specific embodiment of a processing technology for a heat-conducting potting resin for a stator of a new energy vehicle drive motor according to the present invention. It is necessary to point out that the following examples are only used to explain the present invention in more detail, rather than to narrow the scope of protection of the present invention. After reading the present invention, improvements and adjustments made by professionals in this technical field without departing from the concept of the present invention are within the scope of protection required by the present invention.
[0023] A processing technology for heat-conducting potting resin for stator of drive motor of new energy vehicle comprises the following steps:
[0024] By weight, take the following raw material components:
[0025] Component A: 60-100 parts of bisphenol A solid epoxy resin, 5-10 parts of toughening agent, 300-500 parts of modified filler, 1-3 parts of white carbon black, 7-12 parts of silane coupling agent KH550, 1-2 parts of defoaming agent;
[0026] Component B: 35-60 parts of curing agent, 0.3-0.8 parts of accelerator, 200-400 parts of modified filler, 1-4 parts of white carbon black, 6-10 parts of silane coupling agent KH550, 1-4 parts of defoaming agent;
[0027] The toughening agent is ethylene-vinyl acetate copolymer, wherein the content of vinyl acetate is 18-25wt.%.
[0028] Preparation of modified filler: Take filler and modifier in a mass ratio of 100-120:1 and add them into a 60% isopropanol solution by volume, and disperse them ultrasonically at 40-55°C for 12-20 minutes. Let the material stand for 10-20 minutes, filter it, and dry the residue in an oven at 80°C. After drying, ball mill it at 350-450r / min for 2-3 hours to obtain the modified filler.
[0029] The modifier is a combination of hydrazine hydrate and trisodium citrate in a mass ratio of 5 to 8:1. The filler is a combination of silicon carbide and hexagonal boron nitride in a mass ratio of 1:6 to 10.
[0030] The defoaming agent is a combination of polyether-modified heptamethyl trisiloxane and ethoxy-modified trisiloxane in a mass ratio of 12 to 20:1.
[0031] The curing agent is any one of dimethylaminopropylamine, dipropylenetriamine and tetraethylenepentamine.
[0032] The accelerator is a combination of dibutyltin dilaurate and stannous octoate in a mass ratio of 3 to 5:1.
[0033] The preparation method of component A is as follows: add the above-mentioned proportion of bisphenol A type solid epoxy resin, toughening agent, modified filler, white carbon black, coupling agent, and defoaming agent into a stirring kettle, and stir until they are completely dispersed; then place the stirred glue solution in a planetary homogenizer for mixing and degassing. After the degassing is completed, component A can be obtained.
[0034] The preparation method of component B is as follows: adding the curing agent, accelerator, modified filler, white carbon black, coupling agent and defoaming agent in the above proportion into a stirring kettle, stirring until they are completely dispersed; then placing the stirred glue solution in a planetary homogenizer for mixing and degassing, and after the degassing is completed, component B is obtained.
[0035] Preparation of thermal conductive potting resin: Mix the prepared component A and component B evenly, vacuum degas for 1 hour, dry the stainless steel mold at 50-70°C, spray 820-NC release agent on the stainless steel mold, pour the thermal conductive potting glue solution, vacuum and cure in an oven, cure at 70-80°C for 1-2 hours, and then cure at 120-150°C for 6-8 hours to obtain the thermal conductive potting resin.
[0036] Example 1
[0037] A processing technology for heat-conducting potting resin for stator of drive motor of new energy vehicle comprises the following steps:
[0038] By weight, take the following raw material components:
[0039] Component A: 60 parts of bisphenol A solid epoxy resin, 5 parts of toughening agent, 300 parts of modified filler, 1 part of white carbon black, 7 parts of silane coupling agent KH550, 1 part of defoaming agent;
[0040] Component B: 35 parts of curing agent, 0.3 parts of accelerator, 200 parts of modified filler, 1 part of white carbon black, 6 parts of silane coupling agent KH550, 1 part of defoaming agent;
[0041] The toughening agent is ethylene-vinyl acetate copolymer, wherein the content of vinyl acetate is 18 wt.%.
[0042] Preparation of modified filler: Take filler and modifier in a mass ratio of 100:1 and add them to a 60% isopropanol solution by volume, and disperse them ultrasonically at 40°C for 12 minutes. Let the material stand for 10 minutes, filter it, and dry the residue in an oven at 80°C. After drying, ball mill it at 350r / min for 2 hours to obtain the modified filler.
[0043] The modifier is a combination of hydrazine hydrate and trisodium citrate in a mass ratio of 5:1. The filler is a combination of silicon carbide and hexagonal boron nitride in a mass ratio of 1:6.
[0044] The defoaming agent is a combination of polyether-modified heptamethyl trisiloxane and ethoxy-modified trisiloxane in a mass ratio of 12:1.
[0045] The curing agent is dimethylaminopropylamine.
[0046] The accelerator is a combination of dibutyltin dilaurate and stannous octoate in a mass ratio of 3:1.
[0047] The preparation method of component A is as follows: add the above-mentioned proportion of bisphenol A type solid epoxy resin, toughening agent, modified filler, white carbon black, coupling agent, and defoaming agent into a stirring kettle, and stir until they are completely dispersed; then place the stirred glue solution in a planetary homogenizer for mixing and degassing. After the degassing is completed, component A can be obtained.
[0048] The preparation method of component B is as follows: adding the curing agent, accelerator, modified filler, white carbon black, coupling agent and defoaming agent in the above proportion into a stirring kettle, stirring until they are completely dispersed; then placing the stirred glue solution in a planetary homogenizer for mixing and degassing, and after the degassing is completed, component B is obtained.
[0049] Preparation of thermal conductive potting resin: Mix the prepared component A and component B evenly, vacuum degas for 1 hour, dry the stainless steel mold at 50-70°C, spray 820-NC release agent on the stainless steel mold, pour the thermal conductive potting glue solution, vacuum and cure in an oven, cure at 70°C for 1 hour, and then cure at 120°C for 6 hours to obtain the thermal conductive potting resin.
[0050] Example 2
[0051] A processing technology for heat-conducting potting resin for stator of drive motor of new energy vehicle comprises the following steps:
[0052] By weight, take the following raw material components:
[0053] Component A: 100 parts of bisphenol A solid epoxy resin, 10 parts of toughening agent, 500 parts of modified filler, 3 parts of white carbon black, 12 parts of silane coupling agent KH550, 2 parts of defoaming agent;
[0054] Component B: 60 parts of curing agent, 0.8 parts of accelerator, 400 parts of modified filler, 4 parts of white carbon black, 10 parts of silane coupling agent KH550, 4 parts of defoaming agent;
[0055] The toughening agent is ethylene-vinyl acetate copolymer, wherein the content of vinyl acetate is 25wt.%.
[0056] Preparation of modified filler: Take filler and modifier in a mass ratio of 120:1 and add them to a 60% isopropanol solution by volume, and disperse them ultrasonically at 55°C for 20 minutes. Let the material stand for 20 minutes, filter it, and dry the residue in an oven at 80°C. After drying, ball mill it at 450r / min for 3 hours to obtain the modified filler.
[0057] The modifier is a combination of hydrazine hydrate and trisodium citrate in a mass ratio of 8:1, and the filler is a combination of silicon carbide and hexagonal boron nitride in a mass ratio of 1:10.
[0058] The defoaming agent is a combination of polyether-modified heptamethyl trisiloxane and ethoxy-modified trisiloxane in a mass ratio of 20:1.
[0059] The curing agent is dimethylaminopropylamine.
[0060] The accelerator is a combination of dibutyltin dilaurate and stannous octoate in a mass ratio of 5:1.
[0061] The preparation method of component A is as follows: add the above-mentioned proportion of bisphenol A type solid epoxy resin, toughening agent, modified filler, white carbon black, coupling agent, and defoaming agent into a stirring kettle, and stir until they are completely dispersed; then place the stirred glue solution in a planetary homogenizer for mixing and degassing. After the degassing is completed, component A can be obtained.
[0062] The preparation method of component B is as follows: adding the curing agent, accelerator, modified filler, white carbon black, coupling agent and defoaming agent in the above proportion into a stirring kettle, stirring until they are completely dispersed; then placing the stirred glue solution in a planetary homogenizer for mixing and degassing, and after the degassing is completed, component B is obtained.
[0063] Preparation of thermal conductive potting resin: Mix the prepared component A and component B evenly, vacuum degassing for 1 hour, dry the stainless steel mold at 70°C, spray 820-NC release agent on the stainless steel mold, pour the thermal conductive potting glue solution, vacuum and cure in an oven, cure at 80°C for 2 hours, and then cure at 150°C for 8 hours to obtain the thermal conductive potting resin.
[0064] Example 3
[0065] A processing technology for heat-conducting potting resin for stator of drive motor of new energy vehicle comprises the following steps:
[0066] By weight, take the following raw material components:
[0067] Component A: 80 parts of bisphenol A solid epoxy resin, 6 parts of toughening agent, 400 parts of modified filler, 2 parts of white carbon black, 10 parts of silane coupling agent KH550, 1.2 parts of defoaming agent;
[0068] Component B: 50 parts of curing agent, 0.5 parts of accelerator, 300 parts of modified filler, 2 parts of white carbon black, 8 parts of silane coupling agent KH550, 2 parts of defoaming agent;
[0069] The toughening agent is ethylene-vinyl acetate copolymer, wherein the content of vinyl acetate is 20wt.%.
[0070] Preparation of modified filler: Take filler and modifier in a mass ratio of 110:1 and add them to a 60% isopropanol solution by volume, and disperse them ultrasonically at 50°C for 18 minutes. Let the material stand for 12 minutes, filter it, and dry the residue in an oven at 80°C. After drying, ball mill it at 400r / min for 2.5 hours to obtain the modified filler.
[0071] The modifier is a combination of hydrazine hydrate and trisodium citrate in a mass ratio of 6:1, and the filler is a combination of silicon carbide and hexagonal boron nitride in a mass ratio of 1:8.
[0072] The defoaming agent is a combination of polyether-modified heptamethyl trisiloxane and ethoxy-modified trisiloxane in a mass ratio of 16:1.
[0073] The curing agent is dimethylaminopropylamine.
[0074] The accelerator is a combination of dibutyltin dilaurate and stannous octoate in a mass ratio of 3 to 5:1.
[0075] The preparation method of component A is as follows: add the above-mentioned proportion of bisphenol A type solid epoxy resin, toughening agent, modified filler, white carbon black, coupling agent, and defoaming agent into a stirring kettle, and stir until they are completely dispersed; then place the stirred glue solution in a planetary homogenizer for mixing and degassing. After the degassing is completed, component A can be obtained.
[0076] The preparation method of component B is as follows: adding the curing agent, accelerator, modified filler, white carbon black, coupling agent and defoaming agent in the above proportion into a stirring kettle, stirring until they are completely dispersed; then placing the stirred glue solution in a planetary homogenizer for mixing and degassing, and after the degassing is completed, component B is obtained.
[0077] Preparation of thermal conductive potting resin: Mix the prepared component A and component B evenly, vacuum degassing for 1 hour, dry the stainless steel mold at 60°C, spray 820-NC release agent on the stainless steel mold, pour the thermal conductive potting glue solution, vacuum and cure in an oven, cure at 75°C for 2 hours, and then cure at 130°C for 7 hours to obtain the thermal conductive potting resin.
[0078] Comparative Example 1: It is basically the same as Example 2, except that the modified filler is missing.
[0079] Comparative Example 2: It is basically the same as Example 2, except that hexagonal boron nitride is missing.
[0080] Comparative Example 3: It is basically the same as Example 2, except that the content of vinyl acetate in the toughening agent ethylene-vinyl acetate copolymer is 15 wt.%.
[0081] Performance index test description: According to the requirements of the scheme, the potting resin obtained in each embodiment and comparative example is tested as follows:
[0082] 1. Viscosity test: measured using a rotational viscometer in accordance with ASTM D2196.
[0083] 2. Thermal conductivity (GB / T29313-2021), tensile strength (ISO R527), flexural strength (ISO R527), prepare specimens of corresponding sizes according to the preparation method of the cured product for testing.
[0084] 3. Hot and cold shock test: Bake the prepared potting resin sample at 150℃ for 1 hour, and then immediately put it into a -40℃ low temperature box and freeze it for 2 hours; then take out the sample, bake it at 150℃ for 1 hour, and then put it into a -40℃ low temperature box and freeze it for 2 hours, and repeat this cycle 10 times.
[0085] Table 1. Performance test results
[0086]
[0087] From the above test results, it can be seen that Examples 1 to 3 are significantly better than Comparative Examples 1 to 3, and it can be seen that the adjustment of the technical solution has obviously resulted in a deteriorated effect.
[0088] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A processing technology for heat-conducting potting resin for stator of driving motor of new energy vehicle, characterized in that: The thermally conductive potting resin comprises the following raw materials in parts by weight: Component A: 60-100 parts of bisphenol A solid epoxy resin, 5-10 parts of toughening agent, 300-500 parts of modified filler, 1-3 parts of white carbon black, 7-12 parts of silane coupling agent KH550, 1-2 parts of defoaming agent; Component B: 35-60 parts of curing agent, 0.3-0.8 parts of accelerator, 200-400 parts of modified filler, 1-4 parts of white carbon black, 6-10 parts of silane coupling agent KH550, and 1-4 parts of defoaming agent.
2. The processing technology of heat-conducting potting resin suitable for stator of driving motor of new energy vehicle according to claim 1 is characterized in that: The toughening agent is ethylene-vinyl acetate copolymer, wherein the content of vinyl acetate is 18-25wt.%.
3. The processing technology of heat-conducting potting resin suitable for stator of driving motor of new energy vehicle according to claim 1 is characterized in that: Preparation of the modified filler: add filler and modifier into isopropanol solution at a mass ratio of 100-120:1, disperse by ultrasonic at 40-55°C, let the material stand, filter, dry the filter residue, and then ball-mill to obtain the modified filler.
4. The processing technology of heat-conducting potting resin suitable for stator of driving motor of new energy vehicle according to claim 3 is characterized in that: The modifier is a combination of hydrazine hydrate and trisodium citrate in a mass ratio of 5 to 8:1; the filler is a combination of silicon carbide and hexagonal boron nitride in a mass ratio of 1:6 to 10.
5. The processing technology of heat-conducting potting resin suitable for stator of driving motor of new energy vehicle according to claim 1 is characterized in that: The defoaming agent is a combination of polyether-modified heptamethyl trisiloxane and ethoxy-modified trisiloxane in a mass ratio of 12 to 20:
1.
6. The processing technology of heat-conducting potting resin suitable for stator of driving motor of new energy vehicle according to claim 1 is characterized in that: The curing agent is any one of dimethylaminopropylamine, dipropylenetriamine and tetraethylenepentamine.
7. The processing technology of heat-conducting potting resin suitable for stator of driving motor of new energy vehicle according to claim 1 is characterized in that: The accelerator is a combination of dibutyltin dilaurate and stannous octoate in a mass ratio of 3 to 5:
1.
8. The processing technology of heat-conducting potting resin for stator of driving motor of new energy vehicle according to any one of claims 1 to 7 comprises the following steps: The preparation method of component A is as follows: add the above-mentioned proportion of bisphenol A type solid epoxy resin, toughening agent, modified filler, white carbon black, coupling agent, and defoaming agent into a stirring kettle, stir until completely dispersed and uniformly defoamed, and after defoaming is completed, component A is obtained; The preparation method of component B is as follows: adding the curing agent, accelerator, modified filler, white carbon black, coupling agent and defoaming agent in the above proportion into a stirring kettle, and stirring evenly; degassing the stirred glue solution uniformly, and after degassing, component B is obtained; The thermal conductive potting resin is prepared by mixing the prepared component A and component B evenly, performing vacuum degassing, drying the stainless steel mold at 50-70° C., spraying a mold release agent on the stainless steel mold, pouring a thermal conductive potting glue solution, evacuating the mold, and curing in an oven, first curing at 70-80° C. for 1-2 hours, and then curing at 120-150° C. for 6-8 hours, to obtain the thermal conductive potting resin.